2020
DOI: 10.1093/jscr/rjaa117
|View full text |Cite
|
Sign up to set email alerts
|

Not such a small diagnosis: small cell carcinoma of the prostate

Abstract: Small cell carcinoma (SCC) is an aggressive malignancy most commonly described in the lung. We present a case of a 61-year-old male who presented with a neck swelling and was subsequently found to have metastatic SCC of the prostate. Clinicians should be aware that it metastasizes early. Unlike conventional prostate adenocarcinoma, it is not a prostate-specific antigen (PSA) secreting tumor hence serum levels do not correlate with disease severity, and a low PSA reading may give false reassurance. In the futur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
1
0
Order By: Relevance
“…Our study adds to the existing case reports and cohort studies that have reported on outcomes from other parts of the world 1,13,14 . For example, Horne et al presented on 800 patients with SCPC from the National Cancer Database, US, diagnosed between 2004 and 2015 15 .…”
Section: Discussionmentioning
confidence: 85%
“…Our study adds to the existing case reports and cohort studies that have reported on outcomes from other parts of the world 1,13,14 . For example, Horne et al presented on 800 patients with SCPC from the National Cancer Database, US, diagnosed between 2004 and 2015 15 .…”
Section: Discussionmentioning
confidence: 85%
“…First-line regimens involve cytotoxic chemotherapy with a platinum agent, including combinations such as cisplatin and etoposide, carboplatin and etoposide, carboplatin and docetaxel, and carboplatin and cabazitaxel [ 2 ]. As prostate cancer that has progressed to small cell carcinoma lacks AR, there is typically no place in therapy for ADT unless patients are presenting de novo, and the biopsy has a large acinar adenocarcinoma component [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there exists a rare and highly aggressive subtype known as small cell carcinoma of the prostate (SCCP). This subtype is considered to be a rare and aggressive form of cancer and accounts for less than 2% of all prostate cancers [ 1 ]. This variant of prostate cancer is marked by its distinctive features, including high-grade malignancy, neuroendocrine differentiation, and a unique clinical presentation [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation